Establishing and Operationalizing an Energy Efficiency Revolving Fund : Scaling Up Energy Efficiency in Buildings in the Western Balkans - Limaye, Dilip; Singh, Jas; Hofer, Kathrin (World Bank Group, Washington, DC, 2014)
An energy efficiency revolving fund (EERF) is a viable option for scaling up energy efficiency (EE) financing in the public sector in the Western Balkans. Under a typical EERF targeting the public sector, loans are provided to public agencies to cover the initial investment costs of EE projects; some of the resulting savings are then used to repay the EERF until the original investment is recovered, plus interest and service charges. The repayments can then be used to finance additional projects, thereby allowing the capital to revolve creating a sustainable financing mechanism. This guidance note is intended for government decision makers interested in establishing such EE revolving funds. It defines the typical structure of such funds, conditions under which they can be useful and effective, ways they can address some of the financing barriers, and implementation options. The note also provides examples, case studies, and lessons learned, and a 'road map' for establishing such funds.